IN VITRO PLANT REGENERATION AND ANTIBACTERIAL ACTIVITY STUDIES ON THREE ENDEMIC SPECIES OF CEROPEGIA - BINISH T; BEN C.P; PAUL RAJ K (International Journal of Pharma and Bio Sciences, 2014)
Plants are important sources of potentially useful structures for the development of new chemotherapeutic agents. To identify the antibacterial activity of Ceropegia juncea, Ceropegia candelabrum var. candelabrum and Ceropegia spiralis in vitro plant extracts of the plant for its antibacterial activity was performed with different solvents (ethanol, aqueous and chloroform) against various human pathogens viz., Staphylococcus aureus, Escherichia coli, Klebsiella pnemoniae and Pseudomonas, by agar well diffusion method. The ethanol extract from the in-vitro plant showed a higher inhibitory effect, a maximum zone of inhibition 1.6 cm (100µl).On the basis of these experimental results, in vitro plants of these Ceropegia species could be considered for further isolation and evaluation as therapeutic antimicrobial.